1983
DOI: 10.1159/000241630
|View full text |Cite
|
Sign up to set email alerts
|

Sites of Action of Light during Phototherapy

Abstract: In order to investigate the main sites of action of phototherapy in the treatment of neonatal jaundice we studied (a) the in vivo and in vitro relationship between the hematocrit and the effectiveness of phototherapy, and (b) the effect of varying the skin area exposed to light. The results show that the hematocrit does not influence in vivo the efficacy of phototherapy, while they confirm that the total skin surface exposed to light is important in determining the effectiveness of light treatment. The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Furthermore, they found photoisomers in only two of their samples, and then only in small quantities. Nonetheless, both early studies (3,6) still demonstrated that the presence of Hb does indeed impact bilirubin photochemistry. In our study, we exposed our samples to a much lower dose (~10 times lower than used in the aforementioned studies) and used the loss of diazo-reactive bilirubin as a measure of bilirubin photoalteration, which is considered indicative of lumirubin formation (1,7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they found photoisomers in only two of their samples, and then only in small quantities. Nonetheless, both early studies (3,6) still demonstrated that the presence of Hb does indeed impact bilirubin photochemistry. In our study, we exposed our samples to a much lower dose (~10 times lower than used in the aforementioned studies) and used the loss of diazo-reactive bilirubin as a measure of bilirubin photoalteration, which is considered indicative of lumirubin formation (1,7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Granati et al (6) used the loss of bilirubin absorbance, which reflects the destruction of the bilirubin chromophore, as their measure of bilirubin photoalteration. Furthermore, they found photoisomers in only two of their samples, and then only in small quantities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed in in vitro irradiation studies that changes in the Hct affect diazo-reactive bilirubin disappearance in blood. Almost a decade elapsed before a clinical study (8) showed a modest decrease in phototherapy efficacy with an increase in Hct, and this was deemed statistically insignificant on the basis of limited data. No further investigations of the question have appeared since then.…”
mentioning
confidence: 99%
“…In 1983, Granati et al (9) showed in vitro that, as hematocrit declined, bilirubin photodegradation increased; however, the correlation was not confirmed in vivo. In another in vitro study, by Lamola et al (4), using a semiempirical skin model, it was confirmed that hemoglobin in the skin competes with bilirubin for absorption of light during phototherapy.…”
Section: Discussionmentioning
confidence: 99%